2000
DOI: 10.4049/jimmunol.165.2.948
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NY-ESO-1 Peptide Analogues Capable of Improved Stimulation of Tumor-Reactive CTL

Abstract: Expression of NY-ESO-1 in a high proportion of different human tumors makes this protein a very attractive vaccine target. NY-ESO-1 peptides, recognized by HLA-A2-restricted CTL, have recently been described. However, it remains unclear how efficiently tumors generate these epitopes, and whether peptide analogues can be used for optimal expansion and activation of NY-ESO-1-specific HLA-A2-restricted CTL. By generating unique CTL clones, we demonstrate that NY-ESO-1-positive tumor cells are efficiently killed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
153
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 23 publications
6
153
1
Order By: Relevance
“…Heteroclitic peptides, selected on the basis of in vitro or in silico testing, contain amino-acid substitutions that increase the stability of the peptide/MHC complex and often generate robust cytotoxic T-cell responses that cross-react with the native peptide epitope. [50][51][52][53][54][55] WT1 has emerged as a potentially important target in PCM, after it was shown that the patients who received DLI following T-cell-depleted allo-HCT developed increased WT1-specific T-cell responses post DLI, which were associated with reduction in paraprotein. 56 An ongoing study at the Memorial Sloan-Kettering Cancer Center targets residual myeloma post auto-HCT with a heteroclitic WT1 peptide vaccine combined with three WT1 SLPs and delivered with montanide and GM-CSF adjuvant.…”
Section: Myeloma Vaccinesmentioning
confidence: 99%
“…Heteroclitic peptides, selected on the basis of in vitro or in silico testing, contain amino-acid substitutions that increase the stability of the peptide/MHC complex and often generate robust cytotoxic T-cell responses that cross-react with the native peptide epitope. [50][51][52][53][54][55] WT1 has emerged as a potentially important target in PCM, after it was shown that the patients who received DLI following T-cell-depleted allo-HCT developed increased WT1-specific T-cell responses post DLI, which were associated with reduction in paraprotein. 56 An ongoing study at the Memorial Sloan-Kettering Cancer Center targets residual myeloma post auto-HCT with a heteroclitic WT1 peptide vaccine combined with three WT1 SLPs and delivered with montanide and GM-CSF adjuvant.…”
Section: Myeloma Vaccinesmentioning
confidence: 99%
“…Ten days after DNA priming, mice were boosted by i.v. injection of recombinant vaccinia virus (rVV) expressing the minigene NY-ESO-1 157-165 containing a Val at position 165 (40). Seven days after vaccinia boosting, mice were killed and splenocytes stimulated in vitro in the presence of 10 M NY-ESO-1 157-165 peptide in medium containing 100 U/ml IL-2 (PeproTech, Rocky Hill, NJ).…”
Section: Murine Ctl Linesmentioning
confidence: 99%
“…21 To overcome this problem, amino acid substitutions have been tested in several tumor antigens, such as NY-ESO-1, gp100 as well as MART-1. 22,23 Several modifications successfully improved the binding affinity for HLA and immunogenicity.…”
Section: Induction Of Gp2-specific Tumor-reactive Ctl By In Vitro Stmentioning
confidence: 99%